Development and Study of an Encryption Algorithm - Nursulu Kapalova; Kairat Sakan; Kunbolat Algazy; Dilmukhanbet Dyusenbayev (Computation, 2022)
A new symmetric block cipher algorithm called AL02 has been developed. The algorithm scheme provides five-round encryption of 128-bit blocks, while the data size at the input and output of the S-box is 8 bits. The main transformation is the F transformation. The difference between the proposed algorithm and the classical scheme is that the F transformation provides the maximum possible dependence of the output vector bits on the input bits and is based on “modulo 2 addition” and a substitution S-box. To assess the strength of the AL02 algorithm, it was programmatically implemented in the C programming language. During the analysis, the cryptographic properties of the developed encryption algorithm were tested. The algorithm was tested for statistical security. For an experimental assessment, in order to ensure that the ciphertext is not inferior to a random sequence in its properties, the well-known sets of statistical tests by NIST (National Institute of Standards and Technology) and Donald Knuth were used. The property of the avalanche effect was also checked. The strength was evaluated using the methods of differential and linear cryptanalysis.